Meta-Analysis: The Impact of Product, Price, Place, and Promotion on Patient Satisfaction - Hafida, Salsabilla Luthfiana Ayu; Hastuti, Rela; Murti, Bhisma; Handayani, Anggun Fitri (Journal of Health Policy and Management, 2025)
Background: A component of effective health care is measuring patient satisfaction. Satisfaction helps in the evaluation of health services from the patient's perspective. In order to compete globally, hospitals need to consider marketing strategies that emphasize understanding customer needs, wants and demands. One of the most common and widely applied marketing concepts in this context is the marketing mix, which includes four main elements, namely product, place, promotion and price. This research aims to estimate the magnitude of the influence of the marketing mix (4P) which includes product, price, place and promotion on patient satisfaction. Subjects and Method: Meta-analysis studies with PICO research questions. Population = general patients. Intervention = high product quality, high promotion, long distance and high price. Comparison = low product quality, lack of promotion, close distance to facilities, and low price. Outcome= Patient satisfaction. Data obtained from Google Scholar, Pubmed, Scopus and ScienceDirect, with the keywords "Product for patient satisfaction" OR "Promotion for patient satisfaction" OR "Price for patient satisfaction" OR "Place for patient satisfaction" AND "Marketing patient satisfaction" OR "Marketing mix patient satisfaction” AND aOR. The effect size used was the Adjusted Odds Ratio (aOR) from multivariate analysis. Data analysis using the Review Manager 5.3 application. Results: This meta-analysis was carried out on 20 primary studies with a cross-sectional design, originating from Turkey, Israel, Saudi Arabia, Ethiopia and Ghana. The sample size was 14,388 people. The meta-analysis results show that patient satisfaction increases with high product quality and is statistically significant (aOR= 2.23; CI 95%= 1.54 to 3.23; p<0.001) and good promotion, although not statistically significant (aOR= 1.42; CI 95 %= 0.75 to 2.71; p= 0.280). Patient satisfaction decreases with distance to a health facility (aOR= 0.55; 95% CI= 0.35 to 0.86; p= 0.009) and high price (aOR= 0.56; 95% CI= 0.38 to 0.81; p= 0.002). Conclusion: Patient satisfaction increases with high product quality and good promotions. Patient satisfaction decreases with distance to the facility and high prices.